MUSE opto-mechanical design and performance - Hénault, F; Bacon, R; Dekker, H; Delabre, B; Djidel, S; Dubois, J; Hubin, N; Lantz, B; Lau, W; Le Louarn, M; Lewis, I; Lizon, J; et al. (2004)
The MUSE (Multi Unit Spectroscopic Explorer) instrument is a second-generation integral-field spectrograph candidate for the VLT, operating in the visible and near IR wavelength range (0.465-0.93 μm). It is combining a large 1' × 1' Field of View with a spectral resolution of 3000 and a spatial resolution of 0.2" coupled to a sophisticated ground-layer Adaptive Optics (AO) system. After a brief summary of the major instrumental requirements, we will focus on the opto-mechanical design of MUSE, including core subsystems such as the Fore-Optics, the Image Slicers and the Spectrographs, the Structure and the Calibration Unit. The most creative trends of the instrument will be underlined, such as the specific choices adopted to reduce the costs, weight and volume of the Slicer and Spectrograph units, that need to be manufactured and installed on the VLT Nasmyth platform into twenty-four replicas. Finally, a realistic estimate of the expected performance (in both throughput and image quality), and the future development program for the forthcoming detailed design phase will be presented.